Sistem Penjualan pada PT Indo Citra Abadi di Jakarta Berbasis Website - Bellia Putri Alfianki; Harfebi Fryonanda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
PT Indo Citra Abadi is a company engaged in the field of supplier or provider of building materials and work safety. There are problems that occur in business processes which about large expenses in terms of communication, accommodation and the sometimes loss of evidence or supporting documents. The purpose of this research is to build a system of information that can make business processes easily and efficient. The final results from this research are creating an application based on website which is used to help business processes in a company. The process is used System Development Life Cycle with Prototype techniques and for modeling using the Unified Modeling Language. Based on the results of testing and evaluation on research, the system that has been built can help the sales process at the company.